Дмитро Захарович Максименко: шлях від куркуля до старости села - Нестеренко, Л. (Сiверянський лiтопис, 2018)
На основі архівних джерел у статті показано трагедію життя репресованого
жителя с. Іванківці Срібнянського району Чернігівської області Дмитра Захаровича
Максименка. На основании обработанных архивных источников, в статье показано трагедию
жителя с. Иванковцы Сребнянского района Черниговской области Д. З. Максименка. Based upon contemporary records article shows the life tragedy of Dmytro
Zakharovych Maksymenko – the citizen of the Ivankivtsi village, Sribnyansky district of
Chernihiv region. Investigators of the SPA (the State Political Administration) initiated a
preliminary investigation against him on November 15, 1930. The man was accused of the fact
that he has systematically campaigned and propagandized among peasants of the Ivankivtsi
village in recent years. Propaganda was aimed at disrupting the activities carried out by the
Soviet authorities in the countryside: collectivization, grain procurement, etc. On March 1,
1931, the Special Council under the Collegium of the SPA of the USSR decreed to imprison
Dmytro Zakharovych Maksymenko for a term of three years and send him to the labor camps.
According to the second decision on arrest, approved on Nov. 16, 1943 by Novozhylov, the
deputy head of the UNCSS in Chernihiv region, the man was arrested again. The reason for
this was his two-year (October 19, 1941 – September 1943) activity of D. Z. Maksymenko,
as the village head, in favor of the Nazi occupants. The Military Tribunal of the Kiev Military
District in Pryluky on April 11, 1944 sentenced the accused. D. Z. Maksymenko was imprisoned
for a term of 10 years, with the imprisonment in the labor camps, he was also deprived of
public rights for a term of five years.